The Joy of the Modern Home New Media and the Entertainment Market in Argentina, Chile, and Uruguay (1890s-1920s) - Maas, Cecilia (Historamericana, 2022)
Early motion pictures and recorded sound had much more in common with Spotify and Netflix than we might think. Cecilia Maas describes how early twentieth century film and music industries favored niche culture and on-demand consumption. All of this on a global scale: Latin American cities were a key part of the emerging global entertainment market.